Problems Of Directing School Students To Choose A Profession - M.M. Xamrakulova (Euro Asian Journal Publishing, 2024)
In this article, it is said that the teacher's personality plays a very important role in guiding students to the profession. Such a teacher instills in students respect for himself, desire for work, to be like him, to be friends with him are the best wishes, about prospects, about It is discussed that the fundamentals of the desire to share dreams about the profession, the formation of abilities and interests, and the fact that the school is integrally related to the expansion of the initial production readiness of young people, is a decisive condition for directing them to acquire working professions
Keywords: professional diagnosis; professional advice; knowledge